1994
DOI: 10.1016/0370-2693(94)90754-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the radius of a nucleon in interaction with another nucleon

Abstract: We consider a two-nucleon system described by two different skyrmion models that provide attraction for the central NN potential. One of these models is based on the product ansatz and the other on dilaton coupling. Within these models we ask the question, To what degree does the nucleon swell or shrink when the internucleon separation distance is appropriate to attraction or repulsion? We find typically swelling of 3 to 4 percent for central attraction of some 40 to 50 MeV.Comment: Nine pages of plain TeX plu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…[36] for processes dominated by PLC. A similar effect arises within Skyrmion models of the two nucleon interaction [37]. The major effect is the suppression of the probability for PLC in bound nucleon due to the color screening phenomenon [22].…”
Section: Off Shell Effectsmentioning
confidence: 84%
“…[36] for processes dominated by PLC. A similar effect arises within Skyrmion models of the two nucleon interaction [37]. The major effect is the suppression of the probability for PLC in bound nucleon due to the color screening phenomenon [22].…”
Section: Off Shell Effectsmentioning
confidence: 84%
“…The nucleon swelling discussed in this work refers to the increase of the quark confinement size. Such quark confinement enlargement is present in the multiquark cluster models [41][42][43][44][45], while a smaller quark deconfinement is predicted in the Quark-Meson Coupling (QMC) model [46][47][48], and the nuclear potential model [54][55][56]. In the multiquark cluster model, the heavy nuclei favor the formations of large multi-nucleon clusters containing 3N (N = 1, 2, 3...) valence quarks.…”
Section: Nucleon Swelling and The Emc Effectmentioning
confidence: 99%
“…The size of the estimated nucleon swelling from experiments and from various models are listed in Table I. We see that several models predict such effects of a few percent, such as the QMC model [48], the binding potential model [54], the Skyrmion model [55], the quark-nucleon interaction model [56], the chiral quark-soliton model [57], the chiral symmetry restoration model [58], the weak stretching model [59], the PLC-suppression model [60], and the statistical model [61].…”
Section: Nucleon Swelling and The Emc Effectmentioning
confidence: 99%
“…The main difference between the model of refs. [13], [1], [14], [16] and this one (eq. ( 1)) is in the origin of the dilaton.…”
mentioning
confidence: 98%
“…al. [1]. It was found that there is a swelling of the nucleon at intermediate distances between the nucleons which were assumed to preserve their spherical shape.…”
mentioning
confidence: 99%